Faktor – Faktor Penyebab Keinginan Berpindah Pegawai (Studi Pada Pegawai Di Kantor Badan Perencanaan Pembangunan Daerah Kabupaten Puncak Provinsi Papua - Hagabal, Melianus (Universitas Sam Ratulangi, 2017)
For an organization, performance employees is very important, because performance can shows how employees do all anything associated with his work in the organizations performance an organization very determined by conditions and behavior employees owned of these organisations.Phenomena what often happens is performance that has been so good can destroy, both directly and indirectly by various behavior employees.One form of behavior the employee is the wish of move ( turnover intention ) resulting in the decision to left his job. This research result indicates that stress work are influence not significantly to satisfaction work in employees, climate the organisation have significant impact on satisfaction work in employees, job stress significant to the wishes of switch to employees, climate organization insignificant their influence on to the wishes of move, satisfaction work are significant impact on to the wishes of moveKeywords: Job stress, climate organization, satisfaction work , desire move, Papua Province